2021
DOI: 10.3127/ajis.v25i0.2809
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Cashless Society: The Effects of Perceived Convenience and Security on Gamified Mobile Payment Platform Adoption

Abstract: Integrating gamification into mobile payment platform incentivizes people to use digital alternatives for payment and could spur user-centric, platform-mediated interactions. This study examines the relationship between perceived convenience and perceived security on individual users’ intention to use a gamified mobile payment platform in Malaysia; a developing country envisioned to build a cashless society. The partial least square structural equation modeling (PLS-SEM) technique is employed on a final sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…In addition, the findings further promote the notion that perceived convenience would positively influence intention to use. The results were in agreement with similar studies carried out in Malaysia (Lai andLiew, 2021), 10.3389/fpsyg.2022.928735 FIGURE 3 Diagram illustrating the structural model. India (Pal et al, 2021), South Korea (Joo, 2018), and Indonesia (Nurlaily et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the findings further promote the notion that perceived convenience would positively influence intention to use. The results were in agreement with similar studies carried out in Malaysia (Lai andLiew, 2021), 10.3389/fpsyg.2022.928735 FIGURE 3 Diagram illustrating the structural model. India (Pal et al, 2021), South Korea (Joo, 2018), and Indonesia (Nurlaily et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…The role of perceived security on user behaviour has gained scholars' attention. They confirmed that perceived safety acts as the predictor of users' intention in the pre-adoption stage (Chawla & Joshi, 2019;de Luna et al, 2019;Johnson et al, 2018;Lai & Liew, 2021;Lee & Kim, 2020). However, little attention has been given to the study of perceived security in the post-adoption stage (Lim et al, 2019;Sahi et al, 2021).…”
Section: Introductionmentioning
confidence: 86%
“…In terms of convenience, in addition to the convenience of mobile devices and wireless networks in terms of time and place of learning, mobile learning system developers or content providers should provide users with the convenience of accessing the system and content and increase the convenience of the user implementation process in order to enhance the convenience of mobile learning [ 25 ].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Yoon and Kim [ 23 ] extended the concept of perceived convenience to TAM and their study showed that perceived convenience is one of the external variables that affect the acceptance of wireless LANs; Hossain and Prybutok [ 24 ] also found that perceived convenience affects the persistence of radio frequency identification (RFID). Lai and Liew [ 25 ] also found that perceived convenience affects consumers' intention to use gamified mobile payment platforms. Xu et al [ 5 ] also found that perceived convenience affects consumers' continuous intention to use tourism mobile applications in Mainland China.…”
Section: Introductionmentioning
confidence: 99%